Pendidikan Islam Kontemporer di Era Society 5.0 - Ahmad Batsul Mushofi Septian Wahchid; Yahya Ashari (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The Era of Society 5.0 signifies a significant transformation characterized by the integration of digital technology and automation, such as Artificial Intelligence (AI) and the Internet of Things (IoT), into human life. This article examines the implications of this era for Islamic Education, reviewing the emerging challenges and opportunities. Based on the analysis, Society 5.0 brings substantial changes to the education system, including unlimited access to information, personalized learning, and a shift in the teacher's role to that of a facilitator. However, this era also presents serious challenges, such as moral degradation, infrastructure limitations, the digital divide, and the potential decline of direct interaction—which holds significant value in the Islamic educational tradition. Conversely, there are significant opportunities regarding ease of access to knowledge, more creative learning methods, and broader da'wah (propagation) media. To address these issues, this article proposes concrete strategies including the integration of religious curricula with digital technology, the empowerment of teacher competencies, the strengthening of character education and digital ethics, as well as close collaboration between schools and parents. The ultimate goal is to realize Islamic Education with the concept of Rahmatan lil 'Alamin, capable of producing a generation that excels in technology while maintaining spiritual depth and noble character